A subset of metastatic pancreatic ductal adenocarcinomas depends quantitatively on oncogenic Kras/Mek/Erk-induced hyperactive mTOR signalling. Issue 4 (19th January 2015) - Kong, Bo; Wu, Weiwei; Cheng, Tao; Schlitter, Anna Melissa; Qian, Chengjia; Bruns, Philipp; Jian, Ziying; Jäger, Carsten; Regel, Ivonne; Raulefs, Susanne; Behler, Nora; Irmler, Martin; et al.
Abstract : Objective: Oncogenic Kras-activated robust Mek/Erk signals phosphorylate to the tuberous sclerosis complex (Tsc) and deactivates mammalian target of rapamycin (mTOR) suppression in pancreatic ductal adenocarcinoma (PDAC); however, Mek and mTOR inhibitors alone have demonstrated minimal clinical antitumor activity. Design: We generated transgenic mouse models in which mTOR was hyperactivated either through the Kras/Mek/Erk cascade, by loss of Pten or through Tsc1 haploinsufficiency. Primary cancer cells were isolated from mouse tumours. Oncogenic signalling was assessed in vitro and in vivo, with and without single or multiple targeted molecule inhibition. Transcriptional profiling was used to identify biomarkers predictive of the underlying pathway alterations and of therapeutic response. Results from the preclinical models were confirmed on human material. Results: Reduction of Tsc1 function facilitated activation of Kras/Mek/Erk-mediated mTOR signalling, which promoted the development of metastatic PDACs. Single inhibition of mTOR or Mek elicited strong feedback activation of Erk or Akt, respectively. Only dual inhibition of Mek and PI3K reduced mTOR activity and effectively induced cancer cell apoptosis. Analysis of downstream targets demonstrated that oncogenic activity of the Mek/Erk/Tsc/mTOR axis relied on Aldh1a3 function. Moreover, in clinical PDAC samples, ALDH1A3 specifically labelled an aggressive subtype. Conclusions: These results advance our understanding of Mek/Erk-driven mTOR activation and its downstream targets in PDAC, and provide a mechanistic rationale for effective therapeutic matching for Aldh1a3-positive PDACs.